Revolutionizing cancer treatment by boosting dendritic cell vaccine efficacy with graphene oxide - Mohamed, Rafeezul; Ramli, Muhammad Mahyiddin; Reshak, Ali H.; Osman, Nurul Huda; Aziz, Mohd Yusmaidie; Mansor, Mohd Syahir (EnPress Publisher, 2023)
Dendritic cells (DCs) are potent antigen presenting cells that play a crucial role in stimulating T cell responses against cancer. DC vaccines have been utilized as an immunotherapy approach for cancer treatment, but their effectiveness is hampered by challenges in the tumor microenvironment. Graphene oxide (GO), a cutting-edge carbon-based nanomaterial, has shown promise in modulating DC activation and function. This review highlights the recent advancements in DC vaccines and explores how GO can enhance their efficacy for cancer treatment. By leveraging the unique properties of GO, such as its biocompatibility and immunomodulatory effects, DC vaccines can potentially be optimized to overcome the limitations of the tumor microenvironment and achieve improved outcomes in cancer immunotherapy.